Is Europe listening to us? successes and failures of EU citizen consultations - Kies, Raphaël; Nanz, Patrizia (Routledge, 2016)
How can the European Union engage and connect with the people it aims to represent? What initiatives and schemes have been used to engage EU citizens? To what extent can such procedures be considered a move forward towards a more participative and democratic Europe? This collection of internationally recognised specialists in European integration and innovative democratic practices seek to answer these key questions, explore European citizens' thoughts and opinions about the EU and evaluate the governing elite's attempts to engage with the public. It offers critical analysis of EU justifications and strategies for implementing Deliberative Citizens Involvement Projects and focuses on some of the major participative experiences trialled and implemented by EU institutions. By comparing these different attempts to increase and bolster the participation of EU citizens and evaluating their impact the book offers valuable and original material on the civic involvement of EU citizens and the legitimacy of the EU decision making process.